ANALISA PENGARUH MEDITATION THERAPY TERHADAP PENURUNAN KADAR GULA DARAH PADA DIABETESI - Tanty Febriana Audria; Dwi Retnaningsih; Tamrin - (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Background: The condition of the body when relaxation can affect blood glucose levels. The result of preliminary study in February 2018 in the working area of Puskesmas Mijen of Semarang City, obtained data that Diabetesi type 1 as many as 20 peoples. While people with Diabetesi type 2 as many as 89 peoples. Non pharmacology intervention is important to do in an effort to prevent the increase in blood glucose levels, one of them with Meditation Therapy. The aim of this study to determine the effect of Meditation Therapy to a Blood glucose Levels on Diabetesi In the work area of Puskesmas Mijen of Semarang City.Methods: quasy experiment with pretest and post-test without control group design. This sampling techniques are using Cluster sampling technique with combination of Stratified Sampling. The amount of sample are 30 respondents with the estimated drop out 10% to 33 respondents. A guide to do Meditation Therapy using the Standard Operational Procedure (SOP) Meditation Therapy by Theo (2014).This data collection with observation sheet. The data were tested for normality test by using Saphiro Wilk test and analyzed by using Paired t test.Results: After normality test of the data obtained the result that the data were normally distributed so statistical test carried out with Paired t test is known as p-value (sig.2-tailed) = 0,000 which means smaller than a = (0.05). So that, H0 refused and Ha accepted.Conclusions: There is an Effect of Meditation Therapy to a Blood glucose Levels of Diabetesi In Working Area of Puskesmas Mijen of Semarang City.